2019
DOI: 10.1093/ije/dyz071
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep duration, cognition and dementia: a Mendelian randomization study

Abstract: Background Short and long sleep duration have been linked with poorer cognitive outcomes, but it remains unclear whether these associations are causal. Methods We conducted the first Mendelian randomization (MR) study with 77 single-nucleotide polymorphisms (SNPs) for sleep duration using individual-participant data from the UK Biobank cohort (N = 395 803) and summary statistics from the International Genomics of Alzheimer’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 36 publications
1
94
4
1
Order By: Relevance
“…One prior MR study found evidence suggesting longer sleep duration increases cognitive decline. 8 Our findings using an MR framework suggest that genetic risk for AD and incipient AD leads to shorter sleep duration in older ages. Based on our findings of no association between AD-GRS and long sleep, the association between long sleep duration and cognitive impairment is unlikely to be due to the genetic liability for AD.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…One prior MR study found evidence suggesting longer sleep duration increases cognitive decline. 8 Our findings using an MR framework suggest that genetic risk for AD and incipient AD leads to shorter sleep duration in older ages. Based on our findings of no association between AD-GRS and long sleep, the association between long sleep duration and cognitive impairment is unlikely to be due to the genetic liability for AD.…”
Section: Discussionmentioning
confidence: 69%
“…Recent MR study using data from UK Biobank suggested that genetic liability to long sleep duration results in worse cognitive performance. 8 However, this does not rule out that sleep duration may be altered as a result of preclinical AD; and it remains unclear whether shared etiologic factors alter sleep duration prior to cognitive impairment.…”
mentioning
confidence: 99%
“…In the case of systolic blood pressure (SBP) and diastolic blood pressure (DBP), for which independent, non-overlapping summary statistics are not readily available, we undertook a split-sample MR approach 99 whereby we randomly split the UK Biobank sample of unrelated participants of White British ancestry into two subsets. We then re-estimated genetic associations of napping with the top variants identified in the discovery GWAS within each subset, as well as the association of those variants with SBP and DBP within each subset.…”
Section: R T Rmentioning
confidence: 99%
“…Mendelian randomization study (37) used genetic anchors to investigate the causal relationship between sleep duration and cognition in the UK Biobank and found evidence of a non-linear relationship. These insights can inform interventions to improve cognition in older adults, focusing on modifiable factors with the strongest causal effects.…”
Section: Discussionmentioning
confidence: 99%